Genome sequence and evaluation of safety and probiotic potential of Lacticaseibacillus paracasei LC86 and Lacticaseibacillus casei LC89 - Chen, Ting; Zhao, Yunjiao; Fan, Yixuan; Dong, Yao; Gai, Zhonghui (Frontiers in Microbiology, 2025)
AimA comprehensive safety assessment of potential probiotic strains was essential for their application in the food industry. This article systematically evaluated the probiotic characteristics, whole-genome sequence analysis and safety of Lacticaseibacillus paracasei LC86 and Lacticaseibacillus casei LC89.MethodsFirstly, the two strains of lactic acid bacteria selected were identified. Secondly, whole-genome sequencing was performed on LC86 and LC89, and their antibiotic resistance, pathogenicity, and virulence genes were analyzed. We tested various properties of the two strains, included tolerance, cell adhesion, hemolytic activity, catalase activity, gelatin hydrolysis, arginine hydrolysis ability, bile salt hydrolysis capacity, mucin degradation, bioamine, D-/L-lactic acid production and antibiotic susceptibility, to confirm the safety of LC86 and LC89 both in vitro and in vivo. Additionally, we studied the acute toxicity of LC86 and LC89 in mice through a 14-day oral gavage experiment.ResultsThe two strains selected were identified as Lacticaseibacillus paracasei and Lacticaseibacillus casei. The genomes of both LC86 and LC89 were devoid of virulence, antibiotic resistance and pathogenicity genes. LC86 and LC89 exhibited good tolerance to temperature, artificial gastric fluid and artificial intestinal fluid; they were non-hemolytic, their catalase activity, gelatin hydrolysis, arginine hydrolysis and bile salt hydrolysis were all negative. They exhibited the capability to break down proteins and demonstrated sensitivity to a range of antibiotics. The oral LD50 for both LC86 and LC89 in mice was >2 × 1010 CFU/kg.ConclusionThe experimental results above demonstrated the probiotic characteristics and safety of LC86 and LC89, indicating their potential as candidates for probiotics for human and animal applications.